2018
DOI: 10.5771/0943-7444-2018-6-500
|View full text |Cite
|
Sign up to set email alerts
|

Tagging

Abstract: Artworks have a strong emotional impact on the visitors of an exhibition. Many museums and associations opened their collections for access on the web and have studied the potential of social tagging. User data collected by tagging in art social platforms are a precious information source about emotional responses to artworks and a feedback about the way in which users perceives collections. In this paper, we present our new achievements on this topic within the ArsEmotica framework. Our focus is on eliciting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…In cases where tags can be generated in significant quantities and where many of these tags are added to provide access for users at large, their value has been generally regarded as complementary to that of any controlled indexing added by information professionals such as library catalogers. 9 Strengths identified include tags' flexibility and currency, plus their broader accommodation of multiple viewpoints and terminologies. They tend to provide a greater level of "recall," but a lower level of "precision," to use the classical measures of indexing quality.…”
Section: Social Tagging and Social Cataloging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where tags can be generated in significant quantities and where many of these tags are added to provide access for users at large, their value has been generally regarded as complementary to that of any controlled indexing added by information professionals such as library catalogers. 9 Strengths identified include tags' flexibility and currency, plus their broader accommodation of multiple viewpoints and terminologies. They tend to provide a greater level of "recall," but a lower level of "precision," to use the classical measures of indexing quality.…”
Section: Social Tagging and Social Cataloging Studiesmentioning
confidence: 99%
“…11 However, despite the apparent inclusive nature of social tagging, studies have shown how a relatively small number of "supertaggers" tend to produce the lion's share of many "folksonomies" (i.e., the social tagging aggregations). 12 Regardless, no indexing, whether produced by a large number of people or by a single person, is devoid of ideology and bias. 13 Since the 2000s, the complementarity of library cataloging and social tagging has been explored in various studies, many of which have focused on the nature and value of social cataloging.…”
Section: Social Tagging and Social Cataloging Studiesmentioning
confidence: 99%
“…Dessa forma, apresenta-se uma tensão entre a indexação livre e o controle de vocabulário realizado ao mesmo tempo, através de lista de sugestão de termos para indexação que foi preparada por especialistas das áreas de Arquitetura e Biblioteconomia. Vander Wal, criador do termo folksonomia, identificou dois tipos de folksonomia: a folksonomia genérica onde usuários diferentes etiquetam o mesmo objeto com suas próprias tags, e a folksonomia específica onde uma ou poucas pessoas inserem as etiquetas (MOREIRO GONZALEZ, 2011;RAFFERTY, 2018).…”
Section: A Plataforma Arquigrafiaunclassified
“…Furthermore, it is the great variation of perspectives represented that makes a folksonomy potentially useful to all people, regardless of subject knowledge and social and cultural backgrounds (Spiteri 2006, Steele 2009. In her recent review of tagging literature, Rafferty (2018) concludes that tagging, being largely dependent on the taggers, may underperform in comparison to established subject indexing systems, they still "complement, enrich, and… enhance conventional retrieval systems" (p. 510).…”
Section: Previous Researchmentioning
confidence: 99%